Fractal characteristics of full-scale pores and throats in tight sandstone and their application in the analysis of the main controlling factors of a reservoir - Feng, Linjie; Wang, Ruogu; Liu, Nan; Gao, Ze (Frontiers in Earth Science, 2026)
Comprehensive and accurate characterization of pore–throat structures is essential for rational resource assessments and enhanced recovery rates in tight sandstone reservoirs. However, the fractal characteristics of full-scale pores and throats in tight sandstones remain poorly understood. In this study, high-pressure mercury intrusion (HPMI), constant-rate mercury intrusion (CRMI), and nuclear magnetic resonance (NMR) experiments are integrated to provide a full-scale characterization of pore and throat distributions in tight sandstone samples. Fractal dimensions are calculated separately for pores and throats using a wetting-phase model and a 3D capillary tube model. Based on these results, seven pore–throat systems are identified: 1) small bundle-like throats within clay interstitial filler, 2) medium tubular/sheet throats generated by intense compaction, 3) large throats formed by localized dilation of tubular/sheet throats, 4) micropores created by localized constriction of submicron–micron sized intergranular pores, 5) small pores dominated by intragranular dissolution pores, 6) medium pores consisting mainly of residual intergranular pores, and 7) large pores resulting from the combination of moldic pores and residual intergranular pores. Moreover, the reservoir space exhibits a ternary structural characteristic. Both small and medium throats conform to the capillary tube assumption, with mean fractal dimensions of 2.2093 and 2.7214, respectively. Small, medium, and large pores fit the spherical assumption, with mean fractal dimensions of 2.8180, 2.7435, and 2.9825, respectively. Extensive overlap between large throats and micropores forms a beaded pore–throat network for which an appropriate fractal model is currently lacking. The porosity and permeability of the samples in this study are primarily controlled by medium pores and medium throats, followed by small pores, while movable fluid resides predominantly within medium pores. The results suggest that relatively weak compaction is a key factor in the development of high-quality reservoirs in the strata studied. The proposed full-scale classification scheme based on fractal dimensions offers new insights into the microscopic heterogeneity of tight sandstones. Furthermore, the full-scale characterization combined with correlation analysis and pore–throat genesis discrimination provides targeted strategies for exploration of high-quality, tight sandstone reservoirs.